Propagation and Growth Studies of Calligonum polygonoides (Phog) - Kumar, Vnod; Nagavanl, H. C.; Kumar, Devendra; Singh, Ved Pal (Indian Forester, 1996)
Calligonum polygonoides is a sand dune plant which helps in soil binding. Prevents erosion and in stabilization of sand dunes. Phog seeds do not need any special pretreatment for good germination and O.5cm depth is sufficient for sowing. Nov. and Dec. is the best period for seed sowing of get good germination. Propagation of the plant both by seed or vegetatively is very easy and simple.&the plant has adjusted so much to nature for its existence which in turn help the nature by avoiding the desert to grow. We should help the nature and plant by growing and conserving the plant, in turn we can enjoy the greenness instead of sand storms in the desert.